2013
DOI: 10.1002/clen.201100736
|View full text |Cite
|
Sign up to set email alerts
|

Robust Regulation of Alkalinity in Highly Uncertain Continuous Anaerobic Digestion Processes

Abstract: In this paper, a multiple‐input multiple‐output (MIMO) model‐based robust control scheme is proposed for the indirect control of both total alkalinity and the ratio (intermediate alkalinity)/(total alkalinity) by regulating volatile fatty acid concentrations and strong ions concentration, while guaranteeing the so‐called operational stability in anaerobic digestion (AD) processes. The proposed MIMO regulator is an adaptive controller derived from an AD model which incorporates the physicochemical equilibrium o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…Automatic control of reactors is another important aspect developed to assess the effect of acidity and alkalinity in the anaerobic treatment of vinasse [7,14,20]. Mendez-Acosta et al Therefore, the high acidity of vinasses is associated to the VFAs concentration, especially…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Automatic control of reactors is another important aspect developed to assess the effect of acidity and alkalinity in the anaerobic treatment of vinasse [7,14,20]. Mendez-Acosta et al Therefore, the high acidity of vinasses is associated to the VFAs concentration, especially…”
Section: Introductionmentioning
confidence: 99%
“…propionic and butyric acids that can affect the performance of the acetogenic bacteria and methanogenic archaea in the anaerobic digestion process [5,7,12,14,21]. Hence, the treatment of Tequila vinasse by anaerobic digestion requires an adequate control of operation parameters to avoid the VFAs accumulation and to profit the internal alkalinity generated by the anaerobic process itself to ensure the stability of the reactor.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study by Yin et al showed that sunlight-dark conditions can increase the biogas yield from PM [ 3 ]. However, the promoting influence of sunlight-dark conditions on physiological properties of digester, such as the VFAs, TAN, TA and pH, important parameters to be monitored in anaerobic digestion [ 17 20 ], and their effects on biogas production are unclear.…”
Section: Introductionmentioning
confidence: 99%